PEMANFAATAN BATU GUNUNG BOU BUYA KABUPATEN POSO UNTUK CAMPURAN AC-WC - Efraim Bunga; Alpius Alpius; Louise Elizabeth Radjawane (Jurusan Teknik Sipil Universitas Bangka Belitung, 2022)
Road infrastructure development is one of the government's efforts to improve the welfare of the Indonesian people, both in urban areas and in remote areas. The use of local materials for road pavement is recommended that its use can be maximized and can reduce dependence on materials originating from outside the region. Poso Regency is one area that has the potential to have a source of material in the form of mountain rock aggregates. The purpose of the study was to determine the characteristics of the AC-WC mixture using aggregate from Mount Bou Buya, Poso Regency, and to determine the Marshall Immersion value of the AC-WC mixture using rock aggregate from Mount Bou Buya. The 2018 Bina Marga General Specifications are used as a reference in this study. the composition of the mixture for asphalt content of 5% coarse aggregate is 37.50%, fine aggregate is 51.50%, filler is 6%, for asphalt content is 5.5% coarse aggregate is 37.35%, fine aggregate is 51.20%, filler 5 ,95%, for asphalt content of 6%, coarse aggregate is 37.20%, fine aggregate is 50.90%, filler is 5.90%, for asphalt content is 6.5%, coarse aggregate is 37.05%, fine aggregate is 50.60 %, 5.85% filler, for asphalt content of 7%, coarse aggregate is 36.90%, fine aggregate is 50.30%, filler is 5.80%. Marshall Immersion Test (residual Marshall Stability) for the AC – WC mixture using Batu Gunung Bou Buya aggregate, Poso Regency following the General Specifications of Highways 2018, which is 98.04%.